Incidence of Pre-Operative Deep Vein Thrombosis in Patients with Post-Hip Fractures - Dost Mohammad Sohu, Rashid Muhammad, Suresh Kumar, Hafeez Ullah Ghumro, Zamir Ahmed Soomro, Kashif Ali Shaikh, Aijaz Ali Maitlo, Fazallullah Mahar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To estimate the incidence of pre-operative deep vein thrombosis in patients with post-hip fractures. Study Design: Prospective study Place and Duration of Study: Department of Orthopaedic Surgery, Jinnah Postgraduate Medical Centre, Karachi from 1st January 2019 to 31st December 2021. Methodology: One hundred cases hip fractures which were analyzed for incidence of deep vein thrombosis. Three types of tests were used for confirmation including ultrasonography, computed topography and the venography. In cases where identification of deep vein thrombosis was confirmed the implantation of inferior vena cava filters was ensured. Results: There were seven such cases that were having deep vein thrombosis presentation in them while rest of 93% did not have any clinical presentation for deep vein thrombosis with their hip fracture. The incidence of the pre operative deep vein thrombosis was significantly higher in cases that were brought after 72 hours deep vein thrombosis was highest in cases that were within the age bracket of 70-79 years. Conclusion: A lower incidence as 7% of deep vein thrombosis occurs in pre operative cases of hip fracture. Keywords: Incidence, Deep vein thrombosis, Post-hip fracture